2016
DOI: 10.15171/jcs.2016.002
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Support for New Graduated Nurses in Clinical Setting: a Qualitative Study

Abstract: Introduction: Newly graduated nurses experience many stressful situations during transition to practice. The provision of emotional support from more experienced nurses can ameliorate such work-related tension. Studies have not clearly specified the means through which such support could be most effectively provided; therefore the present study was conducted to explore the experiences of qualified nurses around the provision of emotional support to newly graduated nurses. Methods: This qualitative study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 32 publications
4
46
0
Order By: Relevance
“…Students have identi ed lack of clearly stipulated expectations in the clinical learning environment as one of the signi cant challenges that are faced during their clinical practicum [2]. Furthermore, the authors of an Iranian study reported that clinical instructors, who were verbally abusive, created a hostile learning environment that demotivated students to perform procedures in the ward [10]. Contrarywise, authors of another Iranian study reported that avoiding yelling or use of harsh words by clinical instructors when communicating with students in the ward, enhanced positive clinical learning experience [9].…”
Section: Introductionmentioning
confidence: 99%
“…Students have identi ed lack of clearly stipulated expectations in the clinical learning environment as one of the signi cant challenges that are faced during their clinical practicum [2]. Furthermore, the authors of an Iranian study reported that clinical instructors, who were verbally abusive, created a hostile learning environment that demotivated students to perform procedures in the ward [10]. Contrarywise, authors of another Iranian study reported that avoiding yelling or use of harsh words by clinical instructors when communicating with students in the ward, enhanced positive clinical learning experience [9].…”
Section: Introductionmentioning
confidence: 99%
“…Elements of BO, particularly emotional exhaustion, were found to be related to the time spent working in the health care field [11]. First, it is noted that nurses with short field experience want to stand out quickly [12]. In reality this is unlikely; therefore new nurses become disappointed and emotionally burn out much faster than experienced nurses [13].…”
mentioning
confidence: 99%
“…The experience of moving from pre-registration to registered nurse is often recognised as 'transition shock' (Duchsher, 2009) and is something that can cause many nurses to experience significant distress. Such transitions are often fraught with a wide-ranging and diverse range of emotions including anxiety, dread, emotional exhaustion and helplessness (Ebrahimi et al, 2016). For many nurses, this is a time when they can feel at their most vulnerable and experience feelings of insecurity and self-doubt as they adapt to the increasing responsibilities, leading to the 'imposter phenomena' also known as 'imposter syndrome' (Clance and Imes, 1978), although research indicates that nurses of all levels can experience this (Christenson et al, 2016).…”
Section: Transitionmentioning
confidence: 99%